HUBUNGAN PARITAS DAN USIA GESTASI SEBAGAI FAKTOR RESIKO TERHADAP KEJADIAN ANEMIA DEFISIENSI BESI PADA IBU HAMIL - Purba, Cristina Oliviya; Lumbanraja, Alex; Sembiring, Budi (Jurnal Kedokteran Methodist, 2021)
Background: Iron deficiency anemia is the main cause of occurrence in pregnant women, namely anemia in Indonesia with a fairly high incidence so that it causes problems in society. In developing countries iron deficiency anemia causes many deaths in the mother and fetus. The proportion of plasma volume that binds is large when compared to the formation of erythrocytes, which often causes anemia in pregnant women. Method : The research used is the method of literature study or literature review. Data obtained from secondary data using documentation techniques. Data documentation is carried out based on journals related to research variables. Result: There are 5 journals that support the research title. Conclusion: Parity and gestational age as causes of iron deficiency anemia in pregnant women.